Pengembangan Modul dan Assessment Bahasa Inggris Tematik Berbasis Karakter untuk Siswa SD Al Hikmah Semarang - Anjar Setiawan; Eko Heriyanto; Testiana Deni Wijayatiningsih; Dodi Mulyadi; Riana Eka Budiastuti; Anggraini Eka Pratiwi; Syahida Maghfira; Amrizal (Karsa : Jurnal Pengabdian Masyarakat, 2025)
This Community Service Program aims to develop a character-based thematic English module and assessment to enhance the quality of English learning at SD Al Hikmah Semarang. The subjects involved in this program include English teachers and Grade 6 students who participated in the implementation and evaluation stages. The program employed several steps: needs analysis, module and assessment design, expert validation, revision, and limited classroom implementation. Qualitative data were collected through observations, interviews, and field notes. The results indicate that the developed thematic module is contextually relevant, engaging for students, and effective in supporting more communicative and meaningful English learning. The character-based assessment also enables teachers to monitor students’ behavioral development and language skills more systematically. Overall, this program concludes that the character-based thematic module and assessment are feasible to be used as supporting learning materials in primary school English education.